Biochemical characterization of naturally occurring mutations in SARS-CoV-2 RNA-dependent RNA polymerase - Danda, Matěj; Klimešová, Anna; Kušková, Klára; Dostálková, Alžběta; Pagáčová, Aneta; Prchal, Jan; Kapisheva, Marina; Ruml, Tomáš; Rumlová, Michaela (Protein science, 2024)
Since the emergence of SARS-CoV-2, mutations in all subunits of the RNA-dependent RNA polymerase (RdRp) of the virus have been repeatedly reported. Although RdRp represents a primary target for antiviral drugs, experimental studies exploring the phenotypic effect of these mutations have been limited. This study focuses on the phenotypic effects of substitutions in the three RdRp subunits: nsp7, nsp8, and nsp12, selected based on their occurrence rate and potential impact. We employed nano-differential scanning fluorimetry and microscale thermophoresis to examine the impact of these mutations on protein stability and RdRp complex assembly. We observed diverse impacts; notably, a single mutation in nsp8 significantly increased its stability as evidenced by a 13°C increase in melting temperature, whereas certain mutations in nsp7 and nsp8 reduced their binding affinity to nsp12 during RdRp complex formation. Using a fluorometric enzymatic assay, we assessed the overall effect on RNA polymerase activity. We found that most of the examined mutations altered the polymerase activity, often as a direct result of changes in stability or affinity to the other components of the RdRp complex. Intriguingly, a combination of nsp8 A21V and nsp12 P323L mutations resulted in a 50% increase in polymerase activity. To our knowledge, this is the first biochemical study to demonstrate the impact of amino acid mutations across all components constituting the RdRp complex in emerging SARS-CoV-2 subvariants.
Keywords: stabilita proteinů; Coronavirus RNA-Dependent RNA Polymerase; RNA‐dependent RNA polymerase (RdRp); Protein Binding; SARS-CoV-2; virové nestrukturální proteiny; mutace; COVID-19; koronavirová RNA-replikasa; RNA-Dependent RNA Polymerase; SARS‐CoV‐2; RNA-dependentní RNA-polymerasa; Protein Stability; phenotypic effect; Mutation; Humans; mutations; vazba proteinů; Viral Nonstructural Proteins; lidé